Peer Perspectives: Expectations and Satisfaction with Certified Peer Specialist Services - Lien, Ashlee D. (International Journal of Psychosocial Rehabilitation, 2013)
Certified Peer Specialists (CPSs) have experienced recovery from mental illness and are employed in the mental health sys- tem to provide peer support. The importance of CPS services is that support is provided by individuals with shared experi- ence of the disabling power of mental illness. The present study is an initial examination of expectations and satisfaction with CPS services using the expectancy-disconfirmation theory as a conceptual framework. Attendees of the 2009 Kansas Recovery Conference were asked to volunteer for an interview about CPS services, in which 26 CPS service recipients and 146 non-recipients completed interviews. Kruskal-Wallis analyses found no significant differences between expectations of benefits before or after receiving CPS services. Significant positive correlations were found between satisfaction and per- ceived benefits of CPS services. Results of the study provide support for the expectancy-disconfirmation theory, indicating positive initial perceptions of CPS services, and suggesting that peers have consistent expectations of and experiences with CPS services.